Direct and indirect influences of political regimes on corruption. (10th August 2021) - Goel, Rajeev K.; Nelson, Michael A.
Abstract: Objective: This paper studies the direct and indirect impacts of political regimes on corruption. Whereas the interplay of government is fundamental to corrupt acts, the present research sheds new light by showing the direct and indirect influences of dimensions of government structure on corruption. Methods: We employ two different estimation techniques. First, we use OLS regressions, with year and regional dummies. Second, we employ mediation analysis to account for the intermediate role of government size in the relation between government structure and corruption in order to gauge the direct and indirect influences on corruption Results: Results show that government structure, across various dimensions of authoritarian and nonauthoritarian regimes, significantly impacted cross‐national corruption. In particular, a nation's stock of democracy and parliamentary systems lowered corruption, while executive tenure and dimensions of authoritarianism added to corruption. On the other hand, the size of the legislature did not matter when it came to corruption. However, the direct influences of these government structure variables are mitigated or reinforced when the intermediate role of government size is considered in a mediation analysis. Conclusions: The breakdown into the direct and indirect effects on corruption is a novel insight of this work, with useful policy implications.